Long-term Hydrologic Variability in a Large Subtropical Floodplain River: Effects on Commercial Fisheries - Rabuffetti, Ana Pia (2017)
We analysed the effects of decadal and annual hydrologic fluctuations on freshwater fisheries catches in the Middle Paraná River for a period of six decades from the 1930s to the 1980s. The climatic fluctuations in this period strongly affected the hydrology of the Middle Paraná River and the characteristics of its flow regime. The magnitude of floods as well as maximum, minimum and mean water levels increased progressively from 1930s until the 1980s concomitantly with increasing frequency and intensity of El Niño Southern Oscillation events that resulted in differentiation of distinct hydrological periods. The flood pulses were significantly more frequent and of greater magnitudes during the 1970s and 1980s. These large floods resulted in increased commercial fish catches in the 1980s, possibly because of enhanced recruitment. Specifically, large floods increased the commercial fish catches 2 years later. This effect was stronger for species that use floodplain habitats as areas of reproduction and larval nurseries, such as Prochilodus lineatus. We conclude that the natural flow regime of the Paraná River and perhaps other large subtropical rivers must be preserved in order to sustain their productive fisheries.